2019
DOI: 10.1115/1.4045280
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Laminates of Different Material Systems

Abstract: Helicoidal laminates mimicking the laminar structure of the exoskeleton of crustaceans have been reported to resist higher out-of-plane loads than the common cross-ply and quasi-isotropic fiber-reinforced laminates. Some have reported that smaller inter-ply angle improves strength of helicoidal laminates but others have reported the opposite. A few important material parameters that dictate the failure mechanism of helicoidal laminates have recently been proposed based on proof-of-concept carbon fiber-reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The published literature on Bouligand-inspired CFRP structures counts several successful attempts of enhancing the damage tolerance to through-the-thickness loads of 'conventional' CFRP structures [2][3][4][5][6][7][8][9][10][11][12][13]. Some of the most relevant accomplishments gathered from the literature are summarised in Table A.…”
Section: Appendixa Benchmark Of Boulignad-inspired Cfrp Structures Against 'Conventional' Cfrp Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The published literature on Bouligand-inspired CFRP structures counts several successful attempts of enhancing the damage tolerance to through-the-thickness loads of 'conventional' CFRP structures [2][3][4][5][6][7][8][9][10][11][12][13]. Some of the most relevant accomplishments gathered from the literature are summarised in Table A.…”
Section: Appendixa Benchmark Of Boulignad-inspired Cfrp Structures Against 'Conventional' Cfrp Structuresmentioning
confidence: 99%
“…Helicoidal lamination sequences such as Bouligand-inspired architectures (Figure 1a) have been widely investigated in the past years, leading to successful attempts to enhance the damage tolerance to through-the-thickness loads of fibre reinforced composite materials, including glass fibre reinforced composites [1] and, more frequently, Carbon Fibre Reinforced Plastics (CFRPs) [2][3][4][5][6][7][8][9][10][11][12][13]. Motivated by the enhanced damage tolerance under dynamic and quasi-static through-the-thickness loads of tailored CFRP Bouligand solutions with respect to traditional CFRP laminates, there have been recent developments in our knowledge of the mechanics of Bouligand CFRPs [2][3][4][5][6][7][8][9][10][11][12][13]; these, together with recent developments in automated tow placement, have greatly increased the relevance of Bouligand and Bouligand-inspired structures in Engineering practice.…”
Section: Introductionmentioning
confidence: 99%
“…The delamination in each interface rotates by a small angle from the previous one, and these delaminations are linked by matrix splits and spiral upwards, similar to a pair of spiral staircases. This is the unique damage pattern of helicoidally stacked fiber-reinforced laminates and is referred to as a spiraling matrix split [ 18 , 22 , 25 ]. Liu et al [ 25 ] and Suksangpanya et al [ 34 ] reported that spiraling matrix split is a form of matrix crack that grows between fibers.…”
Section: Resultsmentioning
confidence: 99%
“…In the helicoidal structure, the orientation of the fibers in one layer is offset at a slight angle with respect to the fibers in the layer below, forming a spiraling helicoidal configuration. Inspired by these findings, several researchers have conducted studies that mimic the helicoidal structure using CFRP laminates [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The results show that helicoidal layup significantly improves low-speed impact [ 12 , 13 , 14 , 15 , 16 , 17 ] and high-speed impact performance [ 18 ] of CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation